Foam: Imparting Structure to Heterogeneous Catalysis - Makhania, Minaz; Upadhyayula, Sreedevi (ChemBioEng reviews, 2022)
Ceramic and metallic foams have been the subject of research for decades due to their unique and useful properties. The application of foam as a catalytic support is being explored especially for highly endo‐ or exothermic reactions due to better heat transfer. The most widely used catalyst preparation method by wash‐coating for foam‐based catalysts has several drawbacks. Novel preparation methods are reported in the literature. This article provides a critical review of applications of solid foam in heterogeneous catalysis and performance comparison with conventional catalysts, preparation techniques of foam‐based catalysts and methods for performance modeling. The gaps in current research and recommendations to expand the use of foam‐based catalysts to a wider class of reactions by applying innovative methods outlined in the literature are identified. Perspectives on expanding the modeling with solid foam‐based catalysts are also presented. A comprehensive review of applications of solid foam in heterogeneous catalysis is presented, involving preparation methods of foam‐based catalysts with emphasis on the most widely used wash‐coating method. Performance modeling in foam‐based catalysts and a comparison of key performance parameters of solid foam catalysts against conventional catalysts in reactions of industrial importance are given.